Evolutionary and systematic relationships among tuco-tucos of the Ctenomys pundti complex (Rodentia: Octodontidae): A cytogenetic and morphological approach - Tiranti, S.I. (2005)
We present new cytogenetic, morphometric, and sperm morphology data of eight populations belonging to the C. pundti complex from Southern Córdoba and Eastern La Pampa Provinces in Argentina. The diploid numbers ranged from 2n = 44 to 2n = 50, and C- bands revealed a pattern of centromeric and pericentromeric heterochromatin. Comparisons of G-banded karyotypes revealed that the 2n = 44 (Holmberg, Santa Catalina, Sampacho), 2n = 46 (Realicó), 2n = 48 (El Guanaco, Guatraché), 2n = 46-48 (Vicuña Mackenna), and 2n = 50 (Puente Olmos) karyotypes, are closely related. In addition, these karyotypes show a high degree of homology (95%) with C. talarum talarum, despite the fact that five chromosomal rearrangements differentiate both taxa. Discriminant Function Analysis of morphometric data allows to distinguish three clusters: i) the C. mendocinus species group, ii) C. t. talarum, and iii) populations of the C. pundti complex proposed herein. The close phylogenetic relationship between C. talarum and the C. pundti complex, which undoubtedly belong to the same evolutionary lineage, is well supported by two different kinds of evidence: the extensive chromosomal homology and the same symmetric type of sperm. The morphological and chromosomal differences show that these two forms have diverged recently. © Publications Scientifiques du Muséum national d'Histoire naturelle.